Pemberian Edukasi Sebagai Upaya Pencegahan Serta Penanganan Penyakit Degeneratif Kota Batu - Nilasari, Karina; Pramesti, Anisya Nurdania; FZ, Astri Rahima; Putri, Ayu Selfiyana; Ikhtyari, Fatrya Dhea (Jurnal Abdi Mas Adzkia, 2024)
The increase in degenerative diseases is generally caused by an unhealthy lifestyle, such as a diet that does not pay attention to the balance between food intake and needs and a sedentary lifestyle. Some cases of degenerative diseases can also be triggered by a lack of information and knowledge regarding degenerative diseases. Degenerative diseases also have a fairly high mortality rate, according to the Ministry of Health, the number of hypertension cases in 2019 in Indonesia was 63 million, while the death rate reached 427 thousand. So there is a need for health education aimed at reducing degenerative rates. Counseling regarding degenerative diseases was carried out at the Bumiaji Health Center, Pandanrejo Village, Batu City with the elderly who were prolanis participants at the Bumiaji Health Center carried out with a series of activities starting with the provision of a pre-test, counseling, discussion and question and answer, as well as giving a post-test which was carried out in a group forum. This research is a type of quantitative research using survey methods (pre-test and post-test). Data analysis was carried out after data from all respondents was collected and processed using SPSS and Microsoft Excel software. From the results of the data analysis obtained, there was an increase between the pre-test and post-test results. The number of participants who answered correctly during the post-test was greater than the number of participants who answered correctly during the pre-test. From these results it can be said that there is a significant influence due to providing education about degenerative diseases to respondents. With the community service activities that have been carried out, it is hoped that the elderly participants in the Bumiaji Community Health Center Batu City prolanis can increase their knowledge about degenerative diseases and also that they can be more aware of the existence of degenerative diseases that can harm the body.